Examining the performance of DoD and PoD portfolios and determinants in developed and developing countries / Siti Hajar Nadrah Mohamad Ghouse - Mohamad Ghouse, Siti Hajar Nadrah (2018)
Believers of the Efficient Market Hypothesis have argued that it is impossible to make abnormal return since market is efficient. Nevertheless, the contrarian strategists differ to agree. In this setting, this study attempts to examine the ability of Dogs of the Dow (DoD) and Puppies of the Dow (PoD) trading strategies in outperforming the market return. The analyses are done on the DoD and PoD portfolios of 15 individual countries and as well as a group. In addition, this study also investigates determinants (dividend yield, size, gross domestic product and inflation rate) that might affect the returns of these DoD and PoD portfolios. The countries studied are Australia, Hong Kong, Japan, New Zealand, Singapore, South Korea and Taiwan for developed countries and Brazil, Russia, India, China, South Africa, Malaysia, Indonesia and Thailand for developing countries. Yearly data comprising of return, dividend yield, size, gross domestic product and inflation rate are collected from 2000 until 2014. Empirical findings reveal that DoD portfolios outperformed the market in all 15 individual countries studied but the results are only statistically significant in the Russian market. However, when analysis was done as a group, the portfolio returns of DoD beat the market statistically and significantly for developed and developing countries. As for the PoD portfolios, the results indicate that abnormal returns are statistically significant only in share markets of New Zealand, Taiwan and Russia. Similar to the results of DoD portfolios, PoD portfolios also outperformed the share market in the respective countries as a group and these abnormal returns are also statistically significant. The t-test results between the abnormal returns of DoD and PoD portfolios are insignificant, implying that neither DoD nor PoD trading strategies are superior than the other. It is discovered that for the DoD portfolios; dividend yield (in Hong Kong, Singapore, China and Indonesia) size (in Hong Kong, Singapore, South Korea, China, Malaysia and Indonesia) gross domestic product (in Hong Kong, New Zealand, South Korea and India) and inflation rate (in Hong Kong, Taiwan, Malaysia and Thailand) statistically and significantly determine the strategy’s portfolio returns. Positive relationships between dividend yields, gross domestic product and portfolio returns are found in those countries whereas size positively influenced the returns in these countries except for Hong Kong. On the other hand, inflation rate is negatively related to the portfolio returns in these countries. In terms of the PoD portfolio returns, findings indicate that dividend yields in Hong Kong and South Africa; size in Hong Kong, South Korea and Malaysia; gross domestic product in Hong Kong, South Korea India and Malaysia; and inflation rate in Hong Kong, New Zealand, Taiwan, South Africa, Malaysia and Thailand statistically and significantly influence the returns. Dividend yield, size and gross domestic product are positively related with PoD portfolio returns whilst inflation rate indicates an inverse relationship. Overall, this study documented that the determinants vary across countries which could be attributed to the nature of individual share markets and companies, individual economic structure, different government and financial regulatory systems.